Learning Organization Characteristics And Internet Usage In MSC-Status Companies In Malaysia; Perceptions Of Managers And Non-Managers - Abd. Rahim, Mohd. Fairuz (2007)
Major findings of this study indicate that MSC status companies in Malaysia have the basic characteristics of a learning organization. Leadership has significant positive correlation with purpose of Internet usage while culture, structure and process, and managing people as assets have significant positive relationships with both types of Internet tools an dpurpose of Internet usage.